Country Transparency and the Global Transmission of Financial Shocks - Brandao Marques, Luis (IMF Working Papers; Working Paper ;, 2013)
This paper considers the role of country-level opacity (the lack of availability of information) in amplifying shocks emanating from financial centers. We provide a simple model where, in the presence of ambiguity (uncertainty about the probability distribution of returns), prices in emerging markets react more strongly to signals from the developed market, the more opaque the emerging market is. The second contribution is empirical evidence for bond and equity markets in line with this prediction. Increasing the availability of information about public policies, improving accounting standards, and enhancing legal frameworks can help reduce the unpleasant side effects of financial globalization.